TRADISIONALISASI PENDIDIKAN PONDOK PESANTREN MODEREN DI PESANTREN DARUSSALAM KASOMALANG SUBANG - Ni’mawati Ni’mawati (AL-IBANAH, 2021)
This study aims to analyze the traditional criteria that are still present and implemented in the Modern Islamic Boarding Schools in the Darussalam Kasomalang Islamic Boarding School, Subang. This research uses a qualitative approach. While the method used is descriptive-analytical, which describes the traditionalization of Islamic boarding school education in Pesantren Darussalam Kasomalang Subang. The results of this study are: 1) Traditionalization of the Education System of the Darussalam Kasomalang Islamic Boarding School in Subang; a) This Islamic boarding school requires students to attend the Pondok. The cleanliness of the santri and the boarding school is difficult to maintain because of the distance from the water. b) The Darussalam Kasomalang Subang Islamic Boarding School does not have a mosque specifically. There is a gazebo-like building that functions as a mosque and multipurpose building, c) In addition to teaching the Kitab Kuning (Classical Islamic Book), this pesantre also uses its own books for teaching Arabic and English, d) Management of the Darussalam Islamic Boarding School modern management. There is a division of duties including in teaching. 2) Traditionalization of teaching methods at the Darussalam Kasomalang Islamic Boarding School; The bandongan, sorogan, hapalan and majlis ta'lim systems are still applied in the Darussalam Kasomalang Subang Islamic Boarding School.